(untitled) (Research, Society and Development, 2020)
This article discusses the importance of meaningful and collaborative actions for the advancement of educational processes in the school environment, in the context of democratic school management. The aim of this study is to reflect on the importance of democratic school management as a starting point for the ideas of planning, organization and involvement of social actors to strengthen the search for positive and positive transformations in the quality of teaching-learning. As a methodology, bibliographic research was used to analyze this theme, taking as a reference the qualitative approach that promotes brief considerations about the relevance of school management in the educational field, as well as about the importance of the collective democratic construction of school organization decisions. Thus, the instruments were books, periodical articles and laws for this qualitative research. The results show that rethinking educational practices, planning, organization and the involvement of social actors in joint development, fosters mechanisms that favor improvements in quality educational training and gives them meaning. It is concluded that the research allowed the perception that democratic school management in schools is a central point in the formation of education for democracy, under a solidary and integrating aspect.